High-wear-resistance anti-fog lens coating and preparation method thereof
By using a combination coating of nano-silicon dioxide, silicone polymer and other materials on the lens, combined with spray coating technology, the problem of difficulty in taking into account both wear resistance and anti-fog properties of traditional coatings is solved, and efficient and uniform coating preparation is achieved, which significantly improves the performance and service life of the lens.
Patent Information
- Application Number
- CN202411785819.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
AI Technical Summary
The existing lens coatings are difficult to take into account both wear resistance and anti-fog properties, poor coating uniformity, insufficient adhesion, and complex preparation process, resulting in short service life and poor visual effect.
The coating is prepared by spray coating technology to ensure uniformity and adhesion of the coating by using a combination of nanosilicon dioxide, silicone polymers, acrylate copolymers, hard nanoparticles, surfactants and other additives.
It achieves high wear resistance and excellent anti-fog performance, significantly improves the service life of the lens, improves the visual effect, simplifies the preparation process and reduces costs.
Smart Images

Figure BDA0005174010650000161 
Figure BDA0005174010650000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical materials, and in particular to a highly wear-resistant anti-fog lens coating and a preparation method thereof. Background Art
[0002] Anti-fog lens coatings are widely used in a variety of optical products such as glasses, sports goggles, and protective masks. Traditional anti-fog coatings are mainly divided into two categories: hydrophilic and hydrophobic. Hydrophilic anti-fog coatings prevent the formation of fog by absorbing water and forming a uniform water film. Commonly used materials include hydrophilic polymers (such as polyethylene glycol, polyvinyl alcohol, etc.) and hydrophilic nanomaterials (such as nano-silica, nano-titanium oxide, etc.). Hydrophobic anti-fog coatings prevent the formation of fog by reducing the surface tension of water droplets, making them easy to slide off. Commonly used materials include fluorinated polymers, silicones, etc.
[0003] (i) Hydrophilic anti-fog coatings mainly rely on the hydrophilic groups of the material to absorb water and form a uniform water film, thereby avoiding the formation of fog. For example, polyvinyl alcohol (PVA) coatings are widely used on glass and plastic lens surfaces due to their hydrophilicity and good transparency. However, hydrophilic coatings have poor wear resistance and are easily scratched and worn in daily use, causing the anti-fog effect to gradually fail.
[0004] (ii) Hydrophobic anti-fog coatings prevent the formation of fog by reducing surface energy, making water droplets slide off easily. For example, fluorinated polymer (such as perfluoropolyether) coatings have extremely low surface energy and can effectively prevent water droplets from adhering to their surfaces. However, the anti-fog effect of hydrophobic coatings is usually not ideal in high humidity environments, and their preparation cost is high, making them difficult to promote and apply on a large scale.
[0005] Wear-resistant lens coatings extend the service life of lenses by improving the hardness and scratch resistance of the lens surface. Traditional wear-resistant coating materials mainly include acrylic polymers, epoxy resins, silicones, etc. These materials have good mechanical properties and chemical stability, and can effectively resist friction and scratches from the external environment.
[0006] (i) Acrylate polymer coatings are widely used on lens surfaces due to their excellent transparency and weather resistance. For example, copolymers of monomers such as methyl acrylate and ethyl acrylate can form a hard protective film that effectively prevents scratches on the lens surface. However, this type of coating has poor anti-fog performance and is prone to generate fog in a hot and humid environment, affecting visual effects.
[0007] (ii) Epoxy resin coating has excellent adhesion and wear resistance, and can form a dense protective layer on the surface of the lens. However, epoxy resin coating has poor flexibility and is prone to cracking when the temperature changes or is impacted. At the same time, its anti-fog performance is not ideal, especially in high humidity environments.
[0008] (III) Silicone coatings are widely used in optical lenses due to their excellent weather resistance and flexibility. For example, silicone polymers such as methyltrimethoxysilane (MTMS) and γ-aminopropyltriethoxysilane (APTES) can form a protective film with high transparency and good flexibility. However, the wear resistance of silicone coatings is relatively poor and they are easily worn out in daily use, causing the anti-fog effect to gradually fail.
[0009] Existing lens coatings have the following technical defects:
[0010] (1) It is difficult to take into account both wear resistance and anti-fog performance: Existing anti-fog coatings and wear-resistant coatings can usually only show good performance in one aspect, but it is difficult to take into account both wear resistance and anti-fog performance at the same time. For example, although the hydrophilic anti-fog coating has a good anti-fog effect, its wear resistance is poor and it is easy to be scratched and worn in daily use, resulting in the gradual loss of the anti-fog effect. Although the traditional wear-resistant coating can effectively prevent scratches on the lens surface, its anti-fog performance is poor, especially in a high humidity environment, it is easy to generate fog, affecting the wearer's vision.
[0011] (2) Poor coating uniformity: Traditional lens coating preparation methods (such as immersion and drip coating) often fail to ensure coating uniformity, and are prone to problems such as uneven coating thickness and surface defects. These problems not only affect the performance of the coating, but may also lead to poor visual effects of the lens. For example, coating non-uniformity will increase scattering on the lens surface, reduce light transmittance, and thus affect the wearer's visual clarity.
[0012] (3) Poor coating adhesion: The adhesion between the coating and the lens substrate is one of the important factors affecting the coating performance. Existing lens coating materials have certain deficiencies in adhesion, especially in humid or high temperature environments, the coating is prone to fall off or crack, thus affecting its long-term performance. For example, although epoxy resin coating has good adhesion, it is easy to crack when the temperature changes or is impacted, resulting in coating failure.
[0013] (4) Complex preparation process: Traditional lens coating preparation processes are usually complex, requiring multiple steps and long processing time. For example, the preparation of acrylate polymer coatings requires multiple steps such as prepolymerization and curing, which not only increases production costs but also reduces production efficiency. In addition, some complex preparation processes have high requirements for equipment and are difficult to promote and apply in small and medium-sized enterprises. Summary of the invention
[0014] The invention provides a highly wear-resistant anti-fog lens coating and a preparation method thereof. The coating successfully solves the problems of wear resistance and anti-fog of traditional lens coatings through optimized material selection and process design.
[0015] The technical solution adopted by the present invention is: a highly wear-resistant anti-fog lens coating, which includes the following raw materials by weight: 10-30 parts of nano silicon dioxide, 20-40 parts of silicone polymer, 15-25 parts of acrylate copolymer, 5-15 parts of hard nanoparticles, 2-5 parts of surfactant, 1-4 parts of other additives, and 20-40 parts of solvent.
[0016] As a further improvement of the present invention, the particle size of the nano silicon dioxide is 10-50 nanometers.
[0017] As a further improvement of the present invention, the organic silicon polymer is one or more combinations of methyltrimethoxysilane, γ-aminopropyltriethoxysilane, and glycidyltrimethoxysilane.
[0018] As a further improvement of the present invention, the acrylic acid ester copolymer is copolymerized by one or more monomers of methyl acrylate, ethyl acrylate, butyl acrylate and 2-hydroxyethyl methacrylate, wherein the molar ratio of 2-hydroxyethyl methacrylate is 10%-30%.
[0019] As a further improvement of the present invention, the hard nanoparticles are one or more combinations of aluminum oxide, zirconium oxide, silicon carbide, and boron nitride, and the particle size thereof is 5-20 nanometers.
[0020] As a further improvement of the present invention, the surfactant is a nonionic surfactant, preferably a combination of polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, and the mass ratio of polyoxyethylene fatty alcohol ether to polyoxyethylene alkylphenol ether is 1:1.
[0021] As a further improvement of the present invention, the other auxiliary agents include ultraviolet absorbers, antioxidants, mildew inhibitors, leveling agents, dispersants, and cross-linking agents.
[0022] As a further improvement of the present invention, the ultraviolet absorber is one of UV-327, UV-531, UV-9, and UV-P; the antioxidant is one of BHT, TBHQ, and Irganox 1010; the mildew inhibitor is ketoconazole; the leveling agent is one of BYK-333, BYK-354, TEGO Glide 440, and TEGO Flow 370; the dispersant is one of Disperbyk-161, BYK-110, and TEGO Dispers 755W; and the cross-linking agent is one of HDI trimer, IPDI trimer, EpiKote 828, Cymel 303, and Cymel 1123.
[0023] As a further improvement of the present invention, the solvent is a mixture of one or more of ethanol, isopropanol, ethyl acetate, and propylene glycol methyl ether.
[0024] A method for preparing a highly wear-resistant anti-fog lens coating comprises the following steps:
[0025] Step 1: dissolving nano-silicon dioxide and organosilicon polymer in a solvent, stirring, and using ultrasonic treatment for 10-30 minutes to evenly disperse the raw materials to form a mixed solution A;
[0026] Step 2: Add the acrylic acid ester copolymer and the hard nanoparticles into the mixed solution A, and continue stirring for 2-4 hours to obtain a mixed solution B;
[0027] Step 3: Add surfactants and other additives to the mixed solution B, stir with a high-speed stirrer, control the speed at 1000-2000 rpm, stir for 1-3 hours, and fully mix the ingredients to form a mixed solution C;
[0028] Step 4: Spray the mixed solution C evenly on the surface of the lens, and control the coating thickness to 0.1-2 μm, and then dry at 60°C-100°C for 30-80 minutes;
[0029] Step 5: Finally, cure at a temperature of 120°C-150°C for 2-6 hours to obtain the target coating.
[0030] Beneficial effects of the present invention: The highly wear-resistant anti-fog lens coating prepared by the present invention has the following advantages:
[0031] (1) Dual performance improvement: The present invention successfully combines high wear resistance and excellent anti-fog performance, solving the problem that traditional lens coatings are difficult to meet these two requirements at the same time. Through a specific raw material ratio and preparation process, the coating maintains a long-term anti-fog effect while also having excellent wear resistance, significantly improving the service life of the lens.
[0032] (2) Optimization of coating uniformity and transmittance: The present invention adopts spray coating technology to ensure the uniformity of coating thickness, avoiding problems such as uneven coating thickness and surface defects in traditional preparation methods. This not only improves the overall performance of the coating, but also significantly improves the visual effect of the lens, reduces scattering, and increases transmittance, making the wearer's vision clearer.
[0033] (3) Enhanced coating adhesion and stability: The present invention significantly enhances the adhesion between the coating and the lens substrate through optimized material selection and process design. Even in harsh environments such as humidity or high temperature, the coating is not easy to fall off or crack, thereby ensuring the long-term stability and reliability of the coating and extending the service life of the lens.
[0034] (4) Simplifying the preparation process and reducing costs: The preparation method of the present invention is relatively simple, which reduces the preparation steps and processing time, and reduces the production cost. At the same time, the preparation method has low requirements on equipment and is easy to promote and apply in small and medium-sized enterprises, and has broad market prospects. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0036] The invention provides a high-wear-resistant anti-fog lens coating, which is characterized in that it comprises the following raw materials by weight: 10-30 parts of nano silicon dioxide, 20-40 parts of organic silicon polymer, 15-25 parts of acrylate copolymer, 5-15 parts of hard nano particles, 2-5 parts of surfactant, 1-4 parts of other additives and 20-40 parts of solvent.
[0037] The particle size of nano silicon dioxide in the present invention is 10-50 nanometers. The organosilicon polymer is a combination of one or more of methyl trimethoxy silane, γ-aminopropyl triethoxy silane, and glycidyl trimethoxy silane. The acrylate copolymer is copolymerized by one or more of methyl acrylate, ethyl acrylate, and butyl acrylate with 2-hydroxyethyl methacrylate, wherein the molar ratio of 2-hydroxyethyl methacrylate is 10%-30%. The hard nanoparticles are a combination of one or more of aluminum oxide, zirconium oxide, silicon carbide, and boron nitride, and the particle size is 5-20 nanometers. The surfactant is a nonionic surfactant, preferably a combination of polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, and the mass ratio of polyoxyethylene fatty alcohol ether to polyoxyethylene alkylphenol ether is 1:1. Other additives include ultraviolet absorbers, antioxidants, mildew inhibitors, leveling agents, dispersants, and crosslinking agents. The ultraviolet absorber is one of UV-327, UV-531, UV-9, and UV-P; the antioxidant is one of BHT, TBHQ, and Irganox 1010; the mildew inhibitor is ketoconazole; the leveling agent is one of BYK-333, BYK-354, TEGO Glide 440, and TEGO Flow 370; the dispersant is one of Disper byk-161, BYK-110, and TEGO Dispers 755W; and the crosslinking agent is one of HDI trimer, IPDI trimer, EpiKote 828, Cymel 303, and Cymel 1123. The solvent is a mixture of one or more of ethanol, isopropyl alcohol, ethyl acetate, and propylene glycol methyl ether.
[0038] A method for preparing a highly wear-resistant anti-fog lens coating comprises the following steps:
[0039] Step 1: dissolving nano-silicon dioxide and organosilicon polymer in a solvent, stirring, and using ultrasonic treatment for 10-30 minutes to evenly disperse the raw materials to form a mixed solution A;
[0040] Step 2: Add the acrylic acid ester copolymer and the hard nanoparticles into the mixed solution A, and continue stirring for 2-4 hours to obtain a mixed solution B;
[0041] Step 3: Add surfactants and other additives to the mixed solution B, stir with a high-speed stirrer, control the speed at 1000-2000 rpm, stir for 1-3 hours, and fully mix the ingredients to form a mixed solution C;
[0042] Step 4: Spray the mixed solution C evenly on the surface of the lens, and control the coating thickness to 0.1-2 μm, and then dry at 60°C-100°C for 30-80 minutes;
[0043] Step 5: Finally, cure at a temperature of 120°C-150°C for 2-6 hours to obtain the target coating.
[0044] Embodiment 1:
[0045] This embodiment provides a method for preparing a highly wear-resistant anti-fog lens coating, which is specifically as follows.
[0046] Raw material ratio (by weight)
[0047] (a) Nano-silicon dioxide: 20 parts (particle size 30 nanometers);
[0048] (ii) Silicone polymer: 30 parts (methyltrimethoxysilane);
[0049] (iii) Acrylate copolymer: 20 parts (copolymerized from 15 parts of methyl acrylate and 5 parts of 2-hydroxyethyl methacrylate, with the molar ratio of 2-hydroxyethyl methacrylate being 25%);
[0050] (iv) Hard nanoparticles: 10 parts (5 parts of aluminum oxide, 5 parts of zirconium oxide, particle size of 10 nanometers);
[0051] (V) Surfactant: 4 parts (2 parts of polyoxyethylene fatty alcohol ether, 2 parts of polyoxyethylene alkylphenol ether, mass ratio 1:1);
[0052] (vi) Other additives: 3 parts;
[0053] (1) Ultraviolet absorber: 1 part (UV-327)
[0054] (2) Antioxidant: 0.5 parts (BHT)
[0055] (3) Antifungal agent: 0.3 parts (ketoconazole)
[0056] (4) Leveling agent: 0.5 parts (BYK-333)
[0057] (5) Dispersant: 0.4 parts (Disper byk-161)
[0058] (6) Cross-linking agent: 0.3 parts (HDI trimer)
[0059] (VII) Solvent: 30 parts (15 parts ethanol, 15 parts isopropanol).
[0060] Preparation steps
[0061] (i) Preparation of mixed solution A: Add nano-silica and methyltrimethoxysilane to a solvent (a mixture of ethanol and isopropanol), stir with a high-speed stirrer at a speed of 500 rpm for 30 minutes, and use ultrasonic treatment for 20 minutes to uniformly disperse the nano-silica and methyltrimethoxysilane to form a mixed solution A;
[0062] (ii) Preparation of mixed solution B: Adding acrylate copolymer (copolymerized from methyl acrylate and 2-hydroxyethyl methacrylate), aluminum oxide and zirconium oxide to mixed solution A, stirring was continued using a high-speed stirrer at a speed of 800 rpm for 3 hours to ensure that all components were fully mixed to form mixed solution B;
[0063] (III) Preparation of mixed solution C: Add polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, as well as ultraviolet absorber (UV-327), antioxidant (BHT), mildew inhibitor (ketoconazole), leveling agent (BYK-333), dispersant (Disper byk-161), and crosslinking agent (HDI trimer) to mixed solution B, stir with a high-speed stirrer at a speed of 1500 rpm for 2 hours to fully mix the components to form a mixed solution C;
[0064] (IV) Coating and drying: Spray the mixed solution C evenly on the surface of the lens, control the coating thickness to 1 μm, and dry at 80° C. for 50 minutes.
[0065] (V) Curing of coating: The dried lens was placed in an oven at 130°C for curing for 4 hours to obtain the target coating.
[0066] The coating obtained by the above embodiment has excellent wear resistance and anti-fog performance. The coating performs well under the standard wear test, and the wear resistance is much higher than that of ordinary lens coatings; at the same time, the anti-fog effect of the coating surface is significant, and the fog can be quickly eliminated in a short time to keep the lens clear.
[0067] Embodiment 2:
[0068] This embodiment provides a method for preparing a highly wear-resistant anti-fog lens coating, which is specifically as follows.
[0069] Raw material ratio (by weight)
[0070] (i) Nano-silicon dioxide: 25 parts (particle size: 35 nanometers);
[0071] (ii) Silicone polymer: 35 parts (γ-aminopropyltriethoxysilane);
[0072] (iii) Acrylate copolymer: 22 parts (copolymerized from 18 parts of ethyl acrylate and 4 parts of 2-hydroxyethyl methacrylate, with the molar ratio of 2-hydroxyethyl methacrylate being 18%);
[0073] (iv) Hard nanoparticles: 12 parts (6 parts of silicon carbide, 6 parts of boron nitride, particle size 15 nanometers);
[0074] (V) Surfactant: 3 parts (1.5 parts of polyoxyethylene fatty alcohol ether, 1.5 parts of polyoxyethylene alkylphenol ether, mass ratio 1:1);
[0075] (vi) Other additives: 3.5 parts;
[0076] (1) Ultraviolet absorber: 1 part (UV-531)
[0077] (2) Antioxidant: 0.5 parts (Irganox 1010)
[0078] (3) Antifungal agent: 0.5 parts (ketoconazole)
[0079] (4) Leveling agent: 0.5 parts (BYK-354)
[0080] (5) Dispersant: 0.5 parts (TEGO Dispers 755W)
[0081] (6) Cross-linking agent: 0.5 parts (Cymel 303)
[0082] (VII) Solvent: 35 parts (15 parts of ethyl acetate, 20 parts of propylene glycol methyl ether).
[0083] Preparation steps
[0084] (i) Preparation of mixed solution A: Add nano-silica and γ-aminopropyltriethoxysilane to a solvent (a mixture of ethyl acetate and propylene glycol methyl ether), stir with a high-speed stirrer at a speed of 600 rpm for 30 minutes, and simultaneously use ultrasonic treatment for 20 minutes to uniformly disperse the nano-silica and γ-aminopropyltriethoxysilane to form a mixed solution A;
[0085] (ii) Preparation of mixed solution B: Adding acrylate copolymer (copolymerized from ethyl acrylate and 2-hydroxyethyl methacrylate), silicon carbide and boron nitride to mixed solution A, stirring was continued using a high-speed stirrer at a speed of 850 rpm for 3 hours to ensure that all components were fully mixed to form mixed solution B;
[0086] (III) Preparation of mixed solution C: Add polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, as well as ultraviolet absorber (UV-531), antioxidant (Irganox 1010), mildew inhibitor (ketoconazole), leveling agent (BYK-354), dispersant (TEGO Dispers 755W), and crosslinking agent (Cymel303) to mixed solution B, stir with a high-speed stirrer at a speed of 1500 rpm for 2 hours to fully mix the components to form a mixed solution C;
[0087] (IV) Coating and drying: The mixed solution C was evenly coated on the surface of the lens by spray coating, the coating thickness was controlled to be 1.2 μm, and dried at a temperature of 70° C. for 60 minutes.
[0088] (V) Curing of coating: The dried lens is placed in an oven at 140° C. for curing for 4 hours to obtain the target coating.
[0089] The coating obtained by the above embodiment has excellent wear resistance and anti-fog performance. The coating performs well under the standard wear test, and the wear resistance is much higher than that of ordinary lens coatings; at the same time, the anti-fog effect of the coating surface is significant, and the fog can be quickly eliminated in a short time to keep the lens clear.
[0090] Embodiment 3:
[0091] This embodiment provides a method for preparing a highly wear-resistant anti-fog lens coating, which is specifically as follows.
[0092] Raw material ratio (by weight)
[0093] (i) Nano-silicon dioxide: 15 parts (particle size: 20 nanometers);
[0094] (ii) Silicone polymer: 25 parts (γ-aminopropyltriethoxysilane);
[0095] (iii) Acrylate copolymer: 18 parts (copolymerized from 15 parts of ethyl acrylate and 3 parts of 2-hydroxyethyl methacrylate, with the molar ratio of 2-hydroxyethyl methacrylate being 17%);
[0096] (iv) Hard nanoparticles: 10 parts (5 parts of aluminum oxide, 5 parts of zirconium oxide, particle size of 10 nanometers);
[0097] (V) Surfactant: 2.5 parts (1.25 parts of polyoxyethylene fatty alcohol ether, 1.25 parts of polyoxyethylene alkylphenol ether, mass ratio 1:1);
[0098] (vi) Other additives: 2.5 parts;
[0099] (1) Ultraviolet absorber: 0.5 parts (UV-328)
[0100] (2) Antioxidant: 0.4 parts (Irganox 1076)
[0101] (3) Anti-mold agent: 0.4 parts (Mibiqing)
[0102] (4) Leveling agent: 0.4 parts (BYK-358)
[0103] (5) Dispersant: 0.4 parts (TEGO Dispers 740W)
[0104] (6) Cross-linking agent: 0.4 parts (Cymel 327)
[0105] (VII) Solvent: 30 parts (15 parts ethanol, 15 parts isopropanol).
[0106] Preparation steps
[0107] (i) Preparation of mixed solution A: Add nano-silica and γ-aminopropyltriethoxysilane to a solvent (a mixture of ethanol and isopropanol), stir with a high-speed stirrer at a speed of 700 rpm for 30 minutes, and use ultrasonic treatment for 20 minutes to uniformly disperse the nano-silica and γ-aminopropyltriethoxysilane to form a mixed solution A;
[0108] (ii) Preparation of mixed solution B: Adding acrylate copolymer (copolymerized from ethyl acrylate and 2-hydroxyethyl methacrylate), aluminum oxide and zirconium oxide to mixed solution A, stirring was continued using a high-speed stirrer at a speed of 900 rpm for 3 hours to ensure that all components were fully mixed to form mixed solution B;
[0109] (III) Preparation of mixed solution C: Add polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, as well as ultraviolet absorber (UV-328), antioxidant (Irganox 1076), mildew inhibitor (Mibiqing), leveling agent (BYK-358), dispersant (TEGO Dispers 740W), and crosslinking agent (Cymel327) to mixed solution B, stir with a high-speed stirrer at a speed of 1600 rpm for 2 hours to fully mix the ingredients to form a mixed solution C;
[0110] (IV) Coating and drying: The mixed solution C was evenly coated on the surface of the lens by spray coating, the coating thickness was controlled at 0.8 μm, and dried at 90° C. for 40 minutes.
[0111] (V) Curing of coating: The dried lens is placed in an oven at 150° C. for curing for 3 hours to obtain the target coating.
[0112] The coating obtained by the above embodiment has excellent wear resistance and anti-fog performance. The coating performs well under the standard wear test, and the wear resistance is much higher than that of ordinary lens coatings; at the same time, the anti-fog effect of the coating surface is significant, and the fog can be quickly eliminated in a short time to keep the lens clear.
[0113] Performance Testing
[0114] The coatings obtained in Examples 1-3 were subjected to performance tests, including abrasion resistance test, anti-fog test, coating uniformity test, coating adhesion test, light transmittance test, UV resistance test, oxidation resistance test, mildew resistance test, leveling test, and impact resistance test.
[0115] (I) Wear resistance test
[0116] Test method:
[0117] (1) Taber Abrasion Test: Use a Taber abrasion tester to test according to ASTM D4060. Place the coated lens in a test fixture and grind the lens surface with a standard grinding wheel at a certain pressure and speed. Record the change in haze and surface scratches after wear.
[0118] (2) Scratch test: Use a scratch tester (e.g., CETR Nanotribometer) to scratch the coating surface under different loads and observe the changes in scratch depth and width.
[0119] Evaluation indicators:
[0120] (1) Haze change: The wear resistance of the coating is evaluated based on the change in haze before and after wear.
[0121] (2) Surface scratch condition: Observe the scratch condition of the coating surface under a microscope to evaluate its scratch resistance.
[0122] (II) Anti-fog test
[0123] Test method:
[0124] (1) Condensation test: Place the coated lens in a high temperature and high humidity environment (e.g., temperature 40°C, relative humidity 95%) to allow water droplets to condense on the lens surface. Record the formation time and diffusion of the water droplets.
[0125] (2) Thermal shock test: The coated lens is rapidly cooled from a high temperature (e.g. 80°C) to a low temperature (e.g. 10°C) and the surface of the lens is observed to see if fog is generated.
[0126] Evaluation indicators:
[0127] (1) Anti-fog time: The time that the coated lens does not generate fog in a high humidity environment.
[0128] (2) Water droplet diffusion rate: The faster the water droplets diffuse on the surface of the coated lens, the better.
[0129] (3) Fog dissipation time: The time it takes for the fog on the surface of the coated lens to completely dissipate. The shorter the better.
[0130] (III) Coating uniformity test
[0131] Test method:
[0132] (1) Optical microscope observation: Use an optical microscope to observe the uniformity of the coating surface and record the thickness and roughness of the coating.
[0133] (2) Ellipsometer: measures the thickness distribution of the coating to ensure that the coating thickness is uniform.
[0134] Evaluation indicators:
[0135] (1) Coating thickness: The coating thickness should be controlled between 0.1-2 microns, and the thickness distribution should be uniform.
[0136] (2) Surface roughness: Observe the roughness of the coating surface under a microscope to ensure that the coating surface is smooth and has no obvious defects.
[0137] (IV) Coating adhesion test
[0138] Test method:
[0139] (1) Cross-Cut Test: According to ASTM D3359, use a cross-cut knife to draw an 11×11 grid on the coating surface. Then stick a transparent tape on the grid and quickly tear it off to observe the peeling of the coating.
[0140] (2) Heat and humidity aging test: The coated lens is placed in an environment of 85°C and 85% relative humidity. After aging for 1000 hours, a cross-hatch test is performed to evaluate the adhesion of the coating in a heat and humidity environment.
[0141] Evaluation indicators:
[0142] (1) Degree of peeling: Evaluate 0-5 levels based on the results of the cross-hatch method, where 0 means no peeling of the coating and 5 means complete peeling of the coating.
[0143] (2) Adhesion change: The adhesion of the coating after wet heat aging should be equivalent to the initial adhesion, and the change should not exceed 1 level.
[0144] (V) Light transmittance test
[0145] Test method:
[0146] (1) Spectrophotometer: Use a spectrophotometer to measure the transmittance of coated lenses in the visible light range.
[0147] Evaluation indicators:
[0148] (1) Light transmittance: The light transmittance of coated lenses should not be less than 90%.
[0149] (VI) UV resistance test
[0150] Test method:
[0151] (1) Ultraviolet aging test: Place the coated lens under an ultraviolet lamp (e.g., QUV accelerated aging tester) and observe the discoloration and yellowing of the coating after 1000 hours of irradiation.
[0152] (2) Ultraviolet transmittance test: Use a spectrophotometer to measure the transmittance of the coated lens in the ultraviolet range.
[0153] Evaluation indicators:
[0154] (1) Discoloration and yellowing: Coated lenses should not have obvious discoloration and yellowing.
[0155] (2) Ultraviolet transmittance: The transmittance of the coated lens in the ultraviolet range should be less than 2%
[0156] (VII) Antioxidant Test
[0157] Test method:
[0158] (1) Thermal aging test: The coated lens was placed in an oven at 85°C for 1000 hours, and the discoloration and yellowing of the coating were observed.
[0159] (2) Chemical aging test: Place the coated lens in a solution containing an oxidant (e.g. hydrogen peroxide) for 24 hours and observe the discoloration and yellowing of the coating.
[0160] Evaluation indicators:
[0161] (1) Discoloration and yellowing: Coated lenses should not have obvious discoloration and yellowing.
[0162] (VIII) Anti-mildew test
[0163] Test method:
[0164] (1) Anti-mildew grade test: According to GB / T 24128 standard, the coated lens is placed in a mold culture dish and observed for 28 days, and the growth of mold on the coating surface is recorded.
[0165] Evaluation indicators:
[0166] (1) Mildew resistance level: Level 0 means no mold growth, and level 5 means severe mold growth.
[0167] (IX) Leveling test
[0168] Test method:
[0169] (1) Visual inspection: Place the coated lens under strong light and observe whether there is obvious poor leveling on the coating surface.
[0170] (2) Surface roughness test: Use a surface roughness meter to measure the roughness of the coating surface.
[0171] Evaluation indicators:
[0172] (1) Surface roughness: The coating surface should be smooth without obvious defects, and the roughness should be less than 0.1 micron.
[0173] (10) Impact test
[0174] Test method:
[0175] (1) Drop ball impact test: According to ASTM D3763, a drop ball impact tester is used to drop a steel ball freely from a certain height onto the surface of the coated lens to observe whether the coating is cracked or peeled off.
[0176] Evaluation indicators:
[0177] (1) Impact resistance: The coated lens should not show obvious cracking or falling off.
[0178]
[0179]
[0180] It can be seen intuitively from the above table that the highly wear-resistant anti-fog lens coatings obtained in Examples 1-3 performed well in various performance tests, especially in anti-fog and wear resistance, which far exceeded the standards of ordinary lens coatings on the market. This shows that the coating not only has excellent performance in practical applications, but also has high stability and reliability.
[0181] In summary, the highly wear-resistant anti-fog lens coating and its preparation method of the present invention not only reach the industry-leading level in terms of technical indicators, but also show excellent performance in practical applications. Its excellent wear resistance and anti-fog properties make the coating particularly suitable for glasses, diving goggles, car rearview mirrors and other occasions that require a clear field of vision for a long time. In addition, the high light transmittance and anti-ultraviolet and anti-oxidation properties of the coating further ensure the durability and safety of the lens in various environments. Through rigorous testing and verification, the coating technology of the present invention provides a new solution for the lens industry, which is expected to play an important role in improving product performance and user experience.
[0182] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly wear-resistant anti-fog lens coating, characterized in that: The raw materials include the following by weight: 10-30 parts of nano silicon dioxide, 20-40 parts of organic silicon polymer, 15-25 parts of acrylate copolymer, 5-15 parts of hard nano particles, 2-5 parts of surfactant, 1-4 parts of other additives and 20-40 parts of solvent.
2. A highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 10-50 nanometers.
3. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The organic silicon polymer is one or more combinations of methyltrimethoxysilane, γ-aminopropyltriethoxysilane and glycidyltrimethoxysilane.
4. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The acrylic acid ester copolymer is copolymerized by one or more monomers of methyl acrylate, ethyl acrylate and butyl acrylate and 2-hydroxyethyl methacrylate, wherein the molar ratio of 2-hydroxyethyl methacrylate is 10%-30%.
5. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The hard nanoparticles are one or more combinations of aluminum oxide, zirconium oxide, silicon carbide, and boron nitride, and the particle size is 5-20 nanometers.
6. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The surfactant is a nonionic surfactant, preferably a combination of polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, wherein the mass ratio of polyoxyethylene fatty alcohol ether to polyoxyethylene alkylphenol ether is 1:
1.
7. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The other auxiliary agents include ultraviolet absorbers, antioxidants, mildew inhibitors, leveling agents, dispersants, and cross-linking agents.
8. The highly wear-resistant anti-fog lens coating according to claim 7, characterized in that: The ultraviolet absorber is one of UV-327, UV-531, UV-9, and UV-P; the antioxidant is one of BHT, TBHQ, and Irganox 1010; the mildew inhibitor is ketoconazole; the leveling agent is one of BYK-333, BYK-354, TEGO Glide 440, and TEGO Flow 370; the dispersant is one of Disper byk-161, BYK-110, and TEGO Dispers 755W; the cross-linking agent is one of HDI trimer, IPDI trimer, EpiKote 828, Cymel 303, and Cymel 1123.
9. The highly wear-resistant anti-fog lens coating according to claim 1, characterized in that: The solvent is a mixture of one or more of ethanol, isopropanol, ethyl acetate and propylene glycol methyl ether.
10. A method for preparing a highly wear-resistant anti-fog lens coating, characterized in that: The following steps are involved: Step 1: dissolving nano-silicon dioxide and organosilicon polymer in a solvent, stirring, and using ultrasonic treatment for 10-30 minutes to evenly disperse the raw materials to form a mixed solution A; Step 2: Add the acrylic acid ester copolymer and the hard nanoparticles into the mixed solution A, and continue stirring for 2-4 hours to obtain a mixed solution B; Step 3: Add surfactants and other additives to the mixed solution B, stir with a high-speed stirrer, control the speed at 1000-2000 rpm, stir for 1-3 hours, and fully mix the ingredients to form a mixed solution C; Step 4: Spray the mixed solution C evenly on the surface of the lens, and control the coating thickness to 0.1-2 μm, and then dry at 60°C-100°C for 30-80 minutes; Step 5: Finally, cure at a temperature of 120°C-150°C for 2-6 hours to obtain the target coating.